Modern genetics : engineering life - Yount, Lisa. (Milestones in discovery and invention., 2006)
Profiles geneticists and highlights discoveries they have made; includes Gregor Mendel and the laws of inheritance,James Watson and the structure of DNA, and Stanley Cohen and genetic engineering.